IMPLEMENTASI PRINSIP JI’ALAH PADA BISNIS AFFILIATE SHOPEE - Prastika, Rima (Investama : Jurnal Ekonomi dan Bisnis, 2025)
This research explores the suitability of Shopee Affiliate business practices with the principles of ji’alah contracts in the context of Islamic economics. A ji’alah contract is an agreement that provides rewards for services without the burden of task completion, which relates to a results-based affiliate marketing system. This research uses qualitative methods with case studies of Shopee Affiliate practitioners in Mujing Village. Information was collected through in-depth interviews and literature analysis concerning Islamic law. The findings of the research indicate that generally, the Shopee Affiliate practices meet the elements of the ji’alah contract, including clarity regarding the parties involved in the contract (Shopee as the jā’il and the affiliate as the mujta’il), details of the promotion tasks, and provisions regarding commission rewards. However, there is uncertainty (gharar) related to commission payments that depend on consumer actions, which slightly deviates from the traditional concept of ji’alah. This research concludes that this business model can be accepted within the framework of sharia with the note that transparency and fairness must be fulfilled. The implication is that education for business actors is needed, as well as strengthening regulations to ensure full alignment with the principles of Islamic economics.